Using the medicine ball throw test to predict upper limb muscle power: validity evidence - Marco Aurélio Ferreira de Jesus Leite; Jeffer Eidi Sasaki; Camilo Luis Monteiro Lourenço; Hugo Ribeiro Zanetti; Gustavo Ribeiro da Mota; Edmar Lacerda Mendes (Universidade Federal de Santa Catarina, 2020)
Muscle power is the product of muscle force and velocity, which translates into the ability to produce force in a short time interval. Periodic evaluations of strength and power, coupled with training strategies for these capacities, are of great value to athletes and multi-sports coaches, since they are key determinants for team success. Specifically, in rugby, where passing is a predominant and determinant element of sporting success, few field tests are available for assessing upper limb muscle power. The purpose of this point of view is to correct the upper limb power prediction equation previously published by our group and to highlight its concepts and applicability in sports, especially in rugby.